2015
DOI: 10.1007/s00253-015-6678-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of DNA damage and mutation rate by atmospheric and room-temperature plasma (ARTP) and conventional mutagenesis

Abstract: DNA damage is the dominant source of mutation, which is the driving force of evolution. Therefore, it is important to quantitatively analyze the DNA damage caused by different mutagenesis methods, the subsequent mutation rates, and their relationship. Atmospheric and room temperature plasma (ARTP) mutagenesis has been used for the mutation breeding of more than 40 microorganisms. However, ARTP mutagenesis has not been quantitatively compared with conventional mutation methods. In this study, the umu test using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 51 publications
0
78
0
1
Order By: Relevance
“…In particular, the research of CAP as a potential oncotherapeutic approach has thrived over the past decade and the mechanism is been increasingly understood [12][13][14][15][16]. It is widely reported that CAP deactivated more than 20 types of cancer in vitro by inducing apoptosis [17][18][19], cell cycle arrest [20][21][22], endoplasmic reticulum stress [23,24] and DNA damage [25][26][27]. CAP has also been shown to significantly reduce tumor volume in an in vivo murine model following s phase cell cycle arrest and apoptosis [28].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the research of CAP as a potential oncotherapeutic approach has thrived over the past decade and the mechanism is been increasingly understood [12][13][14][15][16]. It is widely reported that CAP deactivated more than 20 types of cancer in vitro by inducing apoptosis [17][18][19], cell cycle arrest [20][21][22], endoplasmic reticulum stress [23,24] and DNA damage [25][26][27]. CAP has also been shown to significantly reduce tumor volume in an in vivo murine model following s phase cell cycle arrest and apoptosis [28].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain mutants with resistance to DPA and/or an analogue, the wild-type strains were treated by the conventional mutation methods, such as ultraviolet (UV) and N-methyl-N-nitro-N-nitroso-guanidine (NTG) (Tani et al, 1985;Sato et al, 2001a;2001b). Compared with these mutation methods, however, an atmospheric and room temperature plasma (ARTP) biological breeding system (Wuxi Tmaxtree Biotechnology Co., Ltd., Wuxi, China) has many outstanding features, such as high positive mutation rate, rapid mutation, and high operation flexibility 2015). For an ARTP breeding system, the DNA of microorganism is destroyed by different chemical reactive species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have further developed genetically engineered umu test systems expressing human phase I drug metabolic enzyme (cytochrome P450) [8] and rat or human phase II drug enzymes (glutathione S -transferase, N -acetyltransfearses, and sulfotransferases) for determination of bioactivation of chemical procarcinogens and promutagens and studies of mechanisms of genotoxicity or carcinogenesis [911]. Finally, we recently published our papers on the application of umu test to photogenotoxicity [12] and flow cytometry analysis [13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, ARTP mutagenesis has not been quantitatively compared with conventional mutation methods. Recently, we developed umu test using a flow-cytometric analysis to quantify the DNA damage caused by ARTP, UV, and chemical (4-NQO and MNNG) treatments in individual viable cells using S. typhimurium NM2009 as the model strain and to determine the mutation rate [13]. The mutation rate was found to be proportional to the corresponding SOS response induced by DNA damage.…”
Section: Introductionmentioning
confidence: 99%